Essential linguistics : what teachers need to know to teach ESL, reading, spelling, grammar - Freeman, David E.; Freeman, Yvonne S. (Heinemann, 2014)
"This edition explains English phonology, morphology, and syntax and the implications for teaching using the International Phonetic Alphabet to prepare students for the Praxis examination including chapters on first and second language acquisition research and theories reviewing ESL teaching methods. With examples, activities, and end-of-chapter applications that link linguistic theory and classroom practice, the Freemans show teachers how to use their new understandings of linguistics to help student learning."